'I knew it wasn't normal, I just didn't know what to do about it': adversity and caregiver support when growing up in a family with Huntington's disease. Issue 2 (1st February 2022) - Kjoelaas, Siri; Jensen, Tine K.; Feragen, Kristin B.
Abstract: Objective: Excessive adversity in childhood can have long-term consequences on health and well-being. One group of children that may be at risk are those who grow up with a parent with Huntington's disease (HD). Despite this, there is little knowledge about how these children are impacted by adversity. We aimed to explore adverse childhood experiences (ACEs) of individuals who grew up with a parent with HD and their perceptions of caregiver support. Design: Semi-structured qualitative interviews of 36 adults and adolescents were analysed using interpretative phenomenological analysis (IPA). Results: First, the analysis revealed a range of frequent adverse events during participants' childhoods, leading to feelings of uncertainty, loss, fear, and a lack of care. Next, how the presence or absence of support had impacted participants' perceptions of these experiences was analysed. Results showed that participants without support were often overwhelmed by feelings of stress, whereas participants with support tolerated adversity better. Conclusion: Findings suggest that children in families with HD can be exposed to a range of adverse experiences. Findings also suggest that sufficient support from a caregiver without HD can buffer or protect against negative consequences of these experiences.